A Case of Delayed Diagnosis of Bilateral Ureteral and Bladder Injury after Laparoscopic Hysterectomy: An Unusual Complication - Maximilien C. Goris-Gbenou; Nicolas Arfi; Abdel Mitach; Sheer Rashed; Jean-Gabriel Lopez (Case Reports in Urology)
The incidence of ureteral and bladder lesions after laparoscopic hysterectomy is the most encountered urinary complication in gynaecological surgery. We report the unusual case of 42-year-old woman who had a delayed diagnosis of bilateral ureteral injury associated with bladder lesion and loose of vaginal suture after undergoing laparoscopic hysterectomy for uterine adenomyosis.